Wavelet transforms of meteorological parameters and gravity waves - Z. Can (Annales Geophysicae, 2005)
The main purpose of this paper is to analyze some characteristics of gravity waves (GWs), and seasonal variations of atmospheric waves over Istanbul by using wavelet techniques. Daily radiosonda data of Istanbul in the troposphere and lower stratosphere (1000hPa-30hPa) between 1993 and 1997 have been considered. Wavelet analysis based on a computer simulation of data is generally close to the real data when Daubechies wavelet series are used. Daily, monthly, seasonal and annual variations of pressure heights, air temperature and deviations from mean values have been analyzed. Variations show the effects of gravity waves for different pressure levels in the troposphere. These waves lead to the meso-scale wave-form structures in spring, autumn and winter. As a result of this study, wavelet series and transforms for data construction, definition of some discontinuities and the local effects on the signal have been compared with the results of previous studies. The most similar structure between temperature, turbulence parameters and geo-potential height deviations has been defined at the 500-hPa pressure level.